Pengaruh Penggunaan Girlband Blackpink Sebagai Brand Ambassador Terhadap Minat Beli Konsumen - Hanifah, Aisyah Fitria (Marcommers : Jurnal Marketing Communication and Advertising, 2023)
This research is motivated by Shopee's inclusion in the e-commerce category which is the most recommended in the MarkPlus Inc survey and this study aims to find out the influence of Blackpink as a Brand Ambassador during the 12.12 Birthday Sale 2018 promotional event on consumers' buying interest. The results of this study used a quantitative approach using the survey method with non-probability sampling type data collection techniques. The results of this study showed a calculated t value of 7.075 greater than the table t of 1.66008. It states that in this study H1 was accepted, the statement that the Brand Ambassador had an effect on buying interest was strengthened by a correlation value of 0.576 which means that two variables have a significant relationship, with a determination coefficient value of 33% of the buying interest variable can be explained by the brand ambassador variable. In this study, it can be concluded that there is an influence of Blackpink as a Brand Ambassador during the Shopee 12.12 Birthday Sale 2018 promotion.